Bioactivity evaluation and composition of extracts from sub-Antarctic macroalgaeMazzaella laminarioidesat distinct development phases - de Freitas, Samantha C.; Berneira, Lucas M.; dos Santos, Marco A. Z.; Poletti, Tais; Mansilla Muñoz, Andres Omar; Astorga España, Maria Soledad; Garcia, Marcelle O.; Hartwig, Daiane D.; Hubner, Silvia de O.; de Pereira, Claudio M. P. (My University, 2020)
Sub-Antarctic macroalgae can be a feasible source of innumerous bioactive compounds that can display important biological activities. In this sense, the aims of this work were to evaluate the chemical composition, antimicrobial activity and cytotoxic potential ofn-hexane extracts from sub-Antarctic seaweedMazzaella laminarioides(Bory) Fredericq at distinct development phases. Results showed that extracts were constituted of as much as 65 distinct compounds that could be distributed mainly among hydrocarbons, fatty acids, sterols and fatty alcohols. Generally, there were significant differences (P < 0.05) in the concentrations of compounds comparing distinct development phases. Antimicrobial evaluation indicated thatn-hexane extracts of cystocarpic and tetrasporophytic phase ofM. laminarioidesinhibited the growth of most organisms tested, reaching minimum inhibitory concentrations of 0.0312 mg mL(-1)againstEnterococcus faecalis(Andrewes and Horder) and 0.25 mg mL(-1)againstAcinetobacter baumannii(Bouvet and Grimont). Cytotoxic evaluation of extracts showed no toxicity to normal cells at concentrations below 1 mg mL(-1). Therefore,M. laminarioidesfrom the sub-Antarctic region had antimicrobial potential that could be explored on further commercial applications.
Keywords: antimicrobial activity; algae; bioactive compounds; cytotoxic assay; gas chromatography; rhodophyta